(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: The study aims to determine the outcomes of mechanochemical ablation (MOCA) with flebogrif to treat varicose veins of the lower extremities. Methods: After the ethical approval from institutional review, this prospective observational study was conducted in the OPD of interventional radiology Shaheed Mohtarma Benazir Bhutto Institute of Trauma (SMBBIT) from ————– to —————-. Through non-probability consecutive sampling, 85 patients aged 18 or above with saphenous vein incompetence and dilated great saphenous vein were included in the present study. The following variables were documented in the recruited patients’ CEAP, VCSS (Clinics Etiology, Anatomy, Pathophysiology Classification, and Venous Clinical Severity Score), and the Analog Pain Scale. Results: 80% of the patient’s CPEA score was C6 before the procedure and after the procedure, 90% of the participants had a C0 score. In 90% of the patients, MOCA was a successful procedure. In 18% of the participants, complications were observed and among them, 67% had experienced pain as a complication. VCSS was improved from the baseline 8.45±3.45 to 4.67±1.2 at 1 month. VAS score was improved from the baseline 6.54±0.56 to 1.3±0.4 at 1 month. Conclusion: The procedures of MOCA, developed by Flebogrif, have demonstrated significant efficacy in the treatment of incompetent varicose veins. In the present investigation, the success rate of MOCA was 91%.